Neonatal near miss and mortality and associated factors: cohort study of births in the city of Rio de Janeiro, RJ, Brazil - Narayani Martins Rocha; Pauline Lorena Kale; Sandra Costa Fonseca; Alexandre dos Santos Brito (Sociedade de Pediatria de São Paulo, 2022)
Abstract Objective: The aim of this study was to investigate factors associated with neonatal near miss and mortality of the live birth cohort in the city of Rio de Janeiro, Brazil, in 2015. Methods: Population-based retrospective cohort of live births (LB) of single pregnancy with 0-27 days of follow-up. Data were obtained from the Brazilian Live Birth and Mortality Information Systems. Logistic regressions with the analytical strategy of hierarchical determination were used for cases of near miss and deaths separately. Results: The cohort was composed of 85,850 LB. For every one thousand LB, about 16 were cases of near miss and six died. Maternal level of education, skin color, and age and adequacy of prenatal care were associated with neonatal near miss; for deaths, presentation of LB at delivery, birth weight, gestational age, and five-minute Apgar score are added. Conclusions: Besides confirming the effect of low birth weight, prematurity, and asphyxia on neonatal death, socioeconomic vulnerability markers - low education level and brown or black skin colors - were associated with neonatal death and near miss. Absent or inadequate prenatal care showed a strong association with both outcomes, being stronger for neonatal death. Investments in the quality of prenatal care and reduction of disparities in health care are necessary in Rio de Janeiro.